Handbook of Christian prophetism in Africa - Aryeh, Daniel Nii Aboagye; Asamoah-Gyadu, J. Kwabena; Holter, Knut (Studies of religion in Africa, 2025)
"More than half a century has passed since the first monographs on African Christian prophetism were published. The prophetic element was only the most dramatic and prominent part of developments that sought to bring the biblical material alive in ways that had not been experienced in the ecclesiology of Western mission Christianity. The ministries of African charismatic figures of the early 20th century were oriented towards the biblical phenomenon of the prophetic, and the related issue of divine or faith healing, sometimes even to the neglect of the use of bio-medical resources. The developments have been interrogated in religious studies, theology, and the sociology and psychology of religion showing how important these churches have been in the African public sphere"--